Detection of the Number of Changes in a Display in Working Memory. - Cowan, Nelson; Hardman, Kyle; Saults, J. Scott; Blume, Christopher L.; Clark, Katherine M.; Sunday, Mackenzie A. (Journal of Experimental Psychology. Learning, Memory & Cognition, 2016)
Here we examine a new task to assess working memory for visual arrays in which the participant must judge how many items changed from a studied array to a test array. As a clue to processing, on some trials in the first 2 experiments, participants carried out a metamemory judgment in which they were to decide how many items were in working memory. Trial-to-trial fluctuations in these working memory storage judgments correlated with performance fluctuations within an individual, indicating a need to include trial-to-trial variation within capacity models (through either capacity fluctuation or some other attention parameter). Mathematical modeling of the results achieved a good fit to a complex pattern of results, suggesting that working memory capacity limits can apply even to judgments that involve an entire array rather than just a single item that may have changed, thus providing the expected conscious access to at least some of the contents of working memory.